Analisis UNCLOS 1982 Terkait Permasalahan Yurisdiksi Negara dan Penegakan Hukum Atas Kapal Berbendera Negara Asing - Zainal Abdul Aziz Hadju (Faculty of Law, Universitas Pattimura, 2021)
International Law has reign most interactions between States in the sea. The practice of illegal transshipment is a serious issue as it falls within both theft mode and smuggling through the transfer of cargo from one ship to another that occurs at sea. Including a crime which committed in the territory of one state but involving parties from another state or more. Law enforcement is a major concern when an offence of some kind of illegal transshipment occurs. The study aims to determine the jurisdiction of states in enforcing laws including in criminal matters that occurred over its sea where the country has sovereign rights, especially when the involvement of 3rd states party in the law enforcement on a ship which not entered into its territory, yet indicately committed a violation of the law in some states water area, this paper also study how the responsibility of 3rd states party towards of flag states of ships who feel harmed. This article was written using normative research methods with a statutory. Historical and conceptual approach explaining efforts from international organizations in resolving the issues of accountability of countries involved in the problem of Illegal Transshipment at sea in the 1982 UNCLOS perspective especially the process of law enforcement and dispute resolution by the International Tribunal for the Law of The Sea (ITLOS).